Scaling up interventions: findings and lessons learned from an external evaluation of Niger's National Initiative to reduce postpartum hemorrhage - Meighan Mary; Ayisha Diop; Wendy R. Sheldon; Aichatou Yenikoye; Beverly Winikoff (BMC, 2019)
Abstract Background Niger has one of the highest maternal mortality ratios in Sub Saharan Africa, of which postpartum hemorrhage is the leading cause. In 2014, Health and Development International and the Ministry of Health of Niger launched an initiative to introduce and scale-up three PPH interventions in health facilities nationwide: misoprostol, uterine balloon tamponade, and the non-pneumatic anti-shock garment. Methods A two-phase mixed-methods evaluation was conducted to assess implementation of the initiative. Health facility assessments, provider interviews, and household surveys were conducted in May 2016 and November 2017. Results All evaluation facilities received misoprostol prevention doses. However, shortages in misoprostol treatment doses, UBT kits, and NASG stock were documented. Health provider training increased while knowledge of each PPH intervention varied. Near-universal uterotonic coverage for PPH prevention and treatment was achieved and sustained throughout the evaluation period. Use of UBT and NASG to manage PPH was rare and differed by health facility type. Among community deliveries, fewer than 22% of women received misoprostol at antenatal care for self-administered prophylaxis. Among those who did, almost all reported taking the drugs for PPH prevention in each phase. Conclusions This study is the first external evaluation of a comprehensive PPH program taking misoprostol, UBT, and NASG to national scale in a low resource setting. Although gaps in service delivery were identified, results demonstrate the complexities of training, managing stock, and implementing system-wide interventions to reach women in varying contexts. The experience provides important lessons for other countries as they develop and expand evidence-based programs for PPH care.